THE ROLE OF THE PEPTIDE INTERMEDIN IN A NOVEL MODEL OF PULMONARY HYPERTENSION. (29th November 2012) - Holmes, D; Bell, D; Harbinson, M; Campbell, M
Abstract : Introduction: Pulmonary hypertension (PH) is characterised by elevated pulmonary arterial pressures, inappropriate apoptosis and vascular remodelling. Animal models fail to replicate such cellular changes. Current therapies target several mediators including endothelin-1 (ET-1). Mortality rates remain high, suggesting other influential biochemical pathways have been overlooked. Intermedin is a potent pulmonary vasodilator acting on receptor complexes comprising calcitonin receptor-like receptor (CRLR) and one of three receptor-activity modifying proteins (RAMPs). Aims: (i) Characterise Intermedin, Adrenomedullin and receptor component distribution across human pulmonary cell-types; (ii) examine effects of simulated hypertension±IMD on pulmonary smooth muscle cell (PSM). Methods: The Flexcell apparatus was used to simulate hypertension. Cell viability was measured by trypan blue assay. Gene expression was quantified by qRT-PCR. Protein levels were assessed by indirect-immunofluorescence techniques and immunoblotting. Results: IMD and AM were most abundant in pulmonary microvascular endothelial cells (PMVEC) and PSM respectively. CRLR was expressed less abundantly than RAMPs1-3; RAMP2 predominated in all cell types. PreproET-1 and preproIMD mRNAs increased maximally 19 fold (p<0.0001, 48 h) and 2-fold (p<0.01, 72 h) respectively in PSM after simulated hypertension. IMD 20 ρmol l-1 improved cell viability in flexed cells and CRLR/RAMP mRNA up-regulation was also observed (p<0.01 vs control), maximally at 48 h. Discussion: IMD and its receptor components were each distributed differentially across human pulmonary cell-types. PH was evidenced in flexed cells by up-regulated ET-1 expression and reduced cell viability. Delayed up-regulation of IMD expression supports a counter-regulatory cytoprotective function for this peptide in human PH.